Theoretical and experimental investigation of the fast- and slow-scale instabilities of a DC-DC converter. - Mazumder, S.K (IEEE Transactions on power electronics)
We use an exact formulation based on nonlinear maps to investigate both the fast-scale and slow-scale instabilities of a voltage-mode buck converter operating in the continuous conduction mode and its interaction with a filter. Comparing the results of the exact model with those of the averaged model shows the shortcomings of the latter in predicting fast-scale instabilities. We show the impact of parasitics on the onset of chaos using a high-frequency model. The experimentally validated theoretical results of this paper provide an improved understanding of the dynamics of the converter beyond the linear regime and this may lead to less conservative control design and newer applications